Typology and Interiority of Cohousing in Europe 1981–2021 - Jorge-Huertas, Virginia De; Jorge-Moreno, Justo De (UI Scholars Hub, 2024)
This work aims to research the connection between cohousing architecture and interiority. For this purpose, the analyses are structured in two phases. The first consists of the characterisation and identification of underlying typologies of European cohousing projects in the last three decades, 1981–2022. The second phase consists of the connection between the interiority concepts (in terms of planimetry, typology, spatial syntax, and interior spaces) and the cohousing architecture in the case studies selected from the first phase, which made it possible to compare cohousing projects and propose future strategies. The research identifies a typology with two clusters of cohousing projects of greater/lesser age and scale. The comparative analysis of the two selected projects, Malta Cohousing (Helsinki) and Schönholzer Strasse (Berlin), provides architectural proposals for compacting the shared and distributed interior spaces on the second floor of the projects, thus making them more usable and finding the points of greatest visibility at the perimeters or in the centre of the interior floor layouts. These proposals could reveal various possibilities for the design of spaces in terms of dynamic forms of the body-space relationships that characterise them and contribute to their improvement and the understanding of the functioning of the occupation and use of the different spaces, whether individual, collective, public, or private. These results fill the existing gap in the literature in terms of a better understanding and analysis of the connection between cohousing architecture and the concept of interiority while also contributing to stakeholders and policymakers in future decision-making.